Analysis of cephalosporins available in India: A pharmacoeconomic perspective - Churihar, Ritesh; Hemant Tanwani; Kamayani Gupta (Asian Journal of Medical Sciences, 2022)
Background: Bacterial infections are one of the most common causes of morbidity and mortality in community and hospital settings. The acceptance of the treatment imposes heavy economic burden on the patients. Due to improper drug policy, different costly preparations of the same brand are ordered and tendered, which pose a sheer wastage of money, ultimately causing burden on tax payers. Aims and Objectives: The present study was planned to evaluate and compare the costs of different brands of various generations of cephalosporin which may be generic or commercial in nature. Materials and Methods: We selected commonly used drugs from different generations of cephalosporins. Cost of drugs (may be generic or commercial or of different formulations) was obtained from latest periodic manuals of Indian Drug Review (INR) and drug today and was analyzed for cost ratio, cost range, and percentage difference among brands from different pharmaceutical companies for oral and parental forms. Correlation among price variations between them was observed by data comparison. Results: Cephalosporins were analyzed for the differences in prices. We not only found wide variation between the cost of generic and commercial preparations but also very wide price range and ratio among the same products from reputed to medium companies. Conclusions: Our study has indicated about the wide differences in the cost of different cephalosporins which are the most commonly prescribed group of antimicrobials. If hospitals across India adopt uniform policy of prescribing cost-effective preparations (brands/generic) only, then the unnecessary economic burden can be significantly reduced.